First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Testing the thermal squeeze hypothesis: Do temperature and invasive species determine vital rates of New Zealand's forest birds? - Ann-Kathrin V. Schlesselmann; John Innes; Susan Walker; Neil Fitzgerald; Graeme Elliott; Adrian Monks (Biological Conservation, 2024)

Flathead grey mullet (Mugil cephalus) juveniles exhibit consistent proactive and reactive stress coping styles - Joel Fitzgerald Linares-Cordova; Sonia Rey-Planellas; Anaïs Boglino; Jessica A. Jimenez-Rivera; Neil J. Duncan; Gustavo Alejandro Rodriguez-Montes de Oca; Zohar Ibarra-Zatarain (Aquaculture, 2024)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Early vigour in wheat: Could it lead to more severe terminal drought stress under elevated atmospheric [CO 2 ] and semi‐arid conditions? - Maryse Bourgault; Heidi A. Webber; Karine Chenu; Garry J. O’Leary; Thomas Gaiser; Stefan Siebert; Fernanda Dreccer; Neil Huth; Glenn J. Fitzgerald; Michael Tausz; Frank Ewert (Global Change Biology, 2020)
Early vigour in wheat is a trait that has received attention for its benefits reducing evaporation from the soil surface early in the season. However, with the growth enhancement common to crops grown under elevated atmospheric CO 2 concentrations (e[CO 2 ]), there is a risk that too much early growth might deplete soil water and lead to more severe terminal drought stress in environments where production relies on stored soil water content. If this is the case, the incorporation of such a trait in wheat breeding programmes might have unintended negative consequences in the future, especially in dry years. We used selected data from cultivars with proven expression of high and low early vigour from the Australian Grains Free Air CO 2 Enrichment (AGFACE) facility, and complemented this analysis with simulation results from two crop growth models which differ in the modelling of leaf area development and crop water use. Grain yield responses to e[CO 2 ] were lower in the high early vigour group compared to the low early vigour group, and although these differences were not significant, they were corroborated by simulation model results. However, the simulated lower response with high early vigour lines was not caused by an earlier or greater depletion of soil water under e[CO 2 ] and the mechanisms responsible appear to be related to an earlier saturation of the radiation intercepted. Whether this is the case in the field needs to be further investigated. In addition, there was some evidence that the timing of the drought stress during crop growth influenced the effect of e[CO 2 ] regardless of the early vigour trait. There is a need for FACE investigations of the value of traits for drought adaptation to be conducted under more severe drought conditions and variable timing of drought stress, a risky but necessary endeavour.

Full Water Quality Monitoring of a Traditional Flow-Through Rainbow Trout Farm - Alexandre Tahar; Alan Kennedy; Richard D. Fitzgerald; Eoghan Clifford; Neil Rowan (Fishes, 2018)
Traditional freshwater rainbow trout farms are still popular in some European countries such as Poland, France and Ireland. These systems generally operate in flow-through configuration. The impact such production systems might have on water quality remains mostly unknown. The present study was set up to fulfil this objective of monitoring water quality on different fish farm locations in order to identify the impacts of the whole farm (comparison of farm inlet and outlet) and at pond scale in order to understand the water quality dynamics and to better understand the impact of multiple water reuse (water passes) in a given pond on water quality. In the absence of any sort of water treatment, an increase in the number of water passes was shown to create an increase in ammonium concentration along the farm. Finally, this traditional flow-through rainbow trout production system was revealed to almost be at its full carrying capacity with respect to internal water quality parameters and fish welfare. To increase fish production, some water treatment techniques (solid/liquid separation, nitrification) would have to be introduced in order to optimize the rearing water quality for fish growth and to minimize the release of pollutants in the receiving water to limit the impact on the environment.

Chemical contamination of soils in the New York City area following Hurricane Sandy - Amy C. Mandigo; Dana J. DiScenza; Alison R. Keimowitz; Neil Fitzgerald (Environmental Geochemistry and Health, 2016)

Response of wheat growth, grain yield and water use to elevated CO 2 under a Free‐Air CO 2 Enrichment ( FACE ) experiment and modelling in a semi‐arid environment - Garry J. O'Leary; Brendan Christy; James Nuttall; Neil Huth; Davide Cammarano; Claudio Stöckle; Bruno Basso; Iurii Shcherbak; Glenn Fitzgerald; Qunying Luo; Immaculada Farre‐Codina; Jairo Palta; et al. (Global Change Biology, 2015)
The response of wheat crops to elevated CO 2 ( eCO 2 ) was measured and modelled with the Australian Grains Free‐Air CO 2 Enrichment experiment, located at Horsham, Australia. Treatments included CO 2 by water, N and temperature. The location represents a semi‐arid environment with a seasonal VPD of around 0.5 kP a. Over 3 years, the observed mean biomass at anthesis and grain yield ranged from 4200 to 10 200 kg ha −1 and 1600 to 3900 kg ha −1 , respectively, over various sowing times and irrigation regimes. The mean observed response to daytime eCO 2 (from 365 to 550 μmol mol −1 CO 2 ) was relatively consistent for biomass at stem elongation and at anthesis and LAI at anthesis and grain yield with 21%, 23%, 21% and 26%, respectively. Seasonal water use was decreased from 320 to 301 mm ( P = 0.10) by eCO 2 , increasing water use efficiency for biomass and yield, 36% and 31%, respectively. The performance of six models (APSIM‐Wheat, APSIM‐Nwheat, CAT‐Wheat, CROPSYST , OLEARY ‐ CONNOR and SALUS ) in simulating crop responses to eCO 2 was similar and within or close to the experimental error for accumulated biomass, yield and water use response, despite some variations in early growth and LAI . The primary mechanism of biomass accumulation via radiation use efficiency ( RUE ) or transpiration efficiency ( TE ) was not critical to define the overall response to eCO 2 . However, under irrigation, the effect of late sowing on response to eCO 2 to biomass accumulation at DC 65 was substantial in the observed data (~40%), but the simulated response was smaller, ranging from 17% to 28%. Simulated response from all six models under no water or nitrogen stress showed similar response to eCO 2 under irrigation, but the differences compared to the dryland treatment were small. Further experimental work on the interactive effects of eCO 2 , water and temperature is required to resolve these model discrepancies.

Water Table Regime Regulates Litter Decomposition in Restiad Peatlands, New Zealand - Beverley R. Clarkson; Tim R. Moore; Neil B. Fitzgerald; Danny Thornburrow; Corinne H. Watts; Steven Miller (Ecosystems, 2014)

Reinvasion by ship rats (Rattus rattus) of forest fragments after eradication - Carolyn M. King; John G. Innes; Dianne Gleeson; Neil Fitzgerald; Tom Winstanley; Barry O’Brien; Lucy Bridgman; Neil Cox (Biological Invasions, 2011)

Rust-proofing wheat for a changing climate - Sukumar Chakraborty; Jo Luck; Grant Hollaway; Glenn Fitzgerald; Neil White (Euphytica, 2011)

Potential mechanisms for achieving agricultural benefits from biochar application to temperate soils: a review - Christopher J. Atkinson; Jean D. Fitzgerald; Neil A. Hipps (Plant and Soil, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)